1994
DOI: 10.1210/endo.135.4.7925099
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Leydig cell development at puberty in the androgen-resistant Tfm mouse.

Abstract: Leydig cells are the major source of androgens in the male, and it is likely that these cells are also targets for androgen action. The role of androgen action in regulating the development of Leydig cell function has been determined using the testicular feminized (Tfm/Y) mouse, which lacks androgen receptors. In Tfm mice, the testes fail to descend at the normal time (25 days), and testicular descent was, therefore, surgically prevented in control (+/Y) animals. The activity of 3 beta-hydroxysteroid dehydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Previous studies with human tissues that confined the presence of ALDH1 in testis to genital skin fibroblasts (GSF) [32, 15, 33]failed to explain the specificity of ALDH1 expression. However both cell types, GSF cells [34]and Leydig cells [35], have androgen receptors, although the expression of Aldh1 has not been investigated before in Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with human tissues that confined the presence of ALDH1 in testis to genital skin fibroblasts (GSF) [32, 15, 33]failed to explain the specificity of ALDH1 expression. However both cell types, GSF cells [34]and Leydig cells [35], have androgen receptors, although the expression of Aldh1 has not been investigated before in Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of NR3C4 in the LC lineage suggests that androgen produced by FLCs, adrenal glands or the LCs themselves might regulate the development and function of LCs. In NR3C4 mutated mice in which there is an androgen insensitivity, reduced differentiation of LCs and decreased LC numbers have been noted (O'Shaughnessy and Murphy, 1993; Murphy et al, 1994). Consistent with this, when PLCs are cultured in vitro , adding androgen greatly increased the efficiency of the cells to differentiate into androgen-producing cells (Hardy et al, 1990).…”
Section: Regulation Of Leydig Cell Developmentmentioning
confidence: 99%
“…Studies by other investigators have found that although there is an impairment in Leydig cell development at puberty, total Leydig cell numbers in adult Tfm mice are more or less the same as those in normal mice (28). Studies by other investigators have found that although there is an impairment in Leydig cell development at puberty, total Leydig cell numbers in adult Tfm mice are more or less the same as those in normal mice (28).…”
Section: Discussionmentioning
confidence: 91%